Acquired B-like antigen - Kanra, Tekin; Pırnar, Aysel (The Turkish Journal of Pediatrics, 1982)
A young woman of the A blood group, with digestive tract pathology and sepsis due to E. coli, showing the acquired B antigen peculiarities is reported.
Keywords: acquired (B-like) antigen; bacterial infection; blood group antigen